Uso del riñón en herradura para trasplante renal. - Grimalt, J.; Resel, Luis; Gómez Vegas, Ángel; Peña Zarzuelo, E. De la; Silmi Moyano, A.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1999)
Sin resumen